Evasão e permanência de estudantes do curso de bacharelado em administração do Instituto Federal da Paraíba (IFPB) - Araújo, Márcia Danyelle Evangelista Freire de (2023)
The policy of racial quotas is a fundamental affirmative action in correcting inequalities and repairing a history of marginalization experienced by the Black population through ensuring access to higher education. However, as important as ensuring access is, it's the follow-up and support of these students that guarantee their continuity and completion of the chosen course. In this context, the overall objective of this research is to analyze the factors contributing to the retention of students who enrolled in the Bachelor of Administration courses at the Federal Institute of Education, Science, and Technology of Paraíba (IFPB - João Pessoa campus) from the semesters between 2019.1 to 2023.1. To achieve this objective, we intend to begin with an investigation into academic data and the socio-demographic profile of the mentioned course to conduct an analysis of the factors contributing to the retention or dropout of these students. Both quota and non-quota students are subjects of our research. Subsequently, we will focus on identifying and analyzing policies to combat dropout rates and ensure retention within the same institution, ultimately proposing a Protocol of Actions to Combat Dropout Rates and/or Academic Monitoring for quota students at IFPB-JP. Our study comprises bibliographic, documentary, and field research in the form of a mixed, exploratory, and descriptive case study approach. To fulfill the study's objectives, we utilized data from the Nilo Peçanha Platform and proprietary data, based on the Scale for the Evaluation of Student Retention (Nakamura; Castelo Branco; Jezine, 2016) adapted to the reality of the researched institution, the target audience, and our specific objectives. During the specified period, out of a total of 202 students admitted through racial quotas, 71 dropped out (35%). In May 2023, the Scale for the Evaluation of Student Retention (Nakamura; Castelo Branco; Jezine, 2016, adapted) was applied, and it was observed, during the study, among both incoming and graduating students, that the main reasons for students to remain in the course are professional prospects and the possibility of social advancement. Course professors play a fundamental role in motivating students to complete their studies. In summary, the study highlights the importance of student motivation for completing the Administration course, as well as the relevance of academic programs, scholarships, and student assistance in student retention. Furthermore, it provides valuable information about the students' socioeconomic profile and their academic conditions, which can assist in implementing strategies to improve student retention and success in the course. Regarding public policies for retention, the Federal Government's Permanent Scholarship Program was found, targeting indigenous or quilombola students regularly enrolled in face-toface undergraduate courses at IFPB; however, there is no indication of this possibility for quota students. Based on the results, a technical product was constructed as a Protocol of Actions to Combat Dropout Rates and/or Academic Monitoring for students, proposed in phases such as planning (or diagnosis), coordination, execution, evaluation, and feedback, aiming to create an updated policy for the retention and belongingness of students admitted through racial quotas within IFPB.